Characterization of double-stranded-RNA-activated kinase that phosphorylates α subunit of eukaryotic initiation factor 2 (eIF-2α) in reticulocyte lysates - Levin, Daniel H. (1980)
Incubation of reticulocyte lysates with low levels of double-stranded (ds) RNA (1-20 ng/ml) activates a cAMP-independent protein kinase (dsI) that phosphorylates the α-subunit (M(r) 38,000) of initiation factor 2 (eIF-2) and produces an inhibition of protein chain initiation similar to that caused by heme deficiency. Activation of dsI from its latent precursor takes place on the ribosomes and requires ATP. dsI can also be activated in ribosomal salt washes and in partially purified preparations of the latent precursor of dsI. In all preparations, activation is accompanied by the ds RNA-dependent phosphorylation of a polypeptide doublet that migrates as bands of 67 and 68.5 kilodaltons (67/68.5) in NaDodSO(4)/acrylamide gels. The rate of phosphorylation of these components in a ribosome salt wash is more rapid than the ds RNA-dependent phosphorylation of eIF-2α. Other polypeptides in the salt wash also undergo ds RNA-dependent phosphorylation, but their significance is not clear. All of these phosphorylations are prevented by high concentrations of poly(I)·poly(C)(20 μg/ml), but not by an antiserum specific for the heme-regulated eIF-2α kinase. Both the latent and activated forms of dsI have been partially purified from a 0.5 M KCl wash of reticulocyte ribosomes. The two species have similar M(r)s (≈120,000) and sedimentation coefficients (≈3.75 S), which suggests that activation of dsI probably does not involve extensive changes. By comparison, the heme-regulated eIF-2α kinase has an M(r) of ≈160,000 and sediments at ≈6.6 S. However, in vitro, dsI and HRI both phosphorylate the same site(s) of eIF-2α. Purified dsI inhibits protein synthesis in hemin-supplemented lysates with the same kinetics induced by the addition of ds RNA; both inhibitions are reversed by eIF-2. dsI that has been activated in the salt wash and then purified does not require ds RNA for expression and no longer displays phosphorylation of the 68.5/67 doublet, which appears to occur only during activation. The data support the view that this component(s) may be the eIF-2α kinase activated by ds RNA.